Factors Influencing Investment Decision in Mutual Funds - Kharel, Tika Ram; Poudel, Shiva Raj; Kharel, Pratik (Exploration अन्वेषण, 2026)
This study investigates the variables influencing funding decisions in mutual funds among Nepali investors. A descriptive and causal-comparative research design was used; both quantitative and qualitative approaches were employed to achieve the study’s objectives. Data collection was carried out through a structured questionnaire, using a convenience sampling method, and the sample size was 384 individual investors of cooperatives. The study employed both descriptive and inferential statistical methods. Descriptive statistic techniques were used to recap demographic character, while inferential statistics, including correlation coefficient and regression analysis, were used to examine the relationships between the dependent variable (decision regarding investments) and the independent variables such as economic position, risk-bearing behaviour, return from investment, and access to information. The results show that economic position, risk-bearing behaviour, and access to information have a significant positive effect on decisions regarding investments, while return from investment showed no significant effect. Particularly, economic position had the highest contribution to the decision regarding investment, indicating its critical role in influencing investor behaviour. The study suggests that mutual fund experts and financial organisations should focus on improving financial literacy and credibility to attract more investors. Future research should explore additional factors, such as psychological influences and peer group pressure and consider comparative research across different investment instruments and demographic groups.